Analisis Brand Switching Produk Minuman Boba Di Lingkungan Kampus Udayana Bukit Jimbaran - Zendrato, Jocelyn Natania; Sadyasmara, Cokorda Bayu; Satriawan, I Ketut (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2025)
Boba drinks have become very popular among young people since 2019. This study aims to determine the characteristics of consumers of boba drink products, especially students of Udayana University in Bukit Jimbaran, to analyze brand switching from several boba drink brands over the next five years, and to determine the long-term market share balance of these boba drink brands. This research was conducted through direct surveys at Chatime, Xiboba, and Mixue in Bukit Jimbaran. The sample was determined using purposive sampling method, data collection was conducted through questionnaires, and the sample size was calculated using Lemeshow’s formula amounting to 100 respondents. The data analysis method was performed using the Markov Chain method with the assistance of POM-QM software. The results indicate that the characteristics of respondents consuming boba drink products are predominantly females aged 18-24 years, with monthly spending on snacks ranging between IDR 100,000 – IDR 299,000, and an average boba drink consumption of once a month. Respondents obtain information about boba drink brands through social media and purchase boba products spontaneously without prior planning based on their own initiative. The market share of boba drink products in the first period was led by Chatime, with a market share of 47%, followed by Mixue (41%), and Xiboba (12%). In the second period, Chatime increased to 47,2%, Mixue (43,6%) and Xiboba decreased to 9,21%. In the third period and beyond, changes in market share occurred among the brands, and by the fifth period, Chatime’s market share increased to 48,6%, while Xiboba secreased to 9,46% and Mixue (41,9%). The equilibrium point is predicted to be reached in the fifth period, with Chatime holding a market share of 48,6%, Xiboba (9,5%), and Mixue (41,9%). Keywords: Brand switching, Markov chain, Chatime, Xiboba, Mixue Minuman boba sangat populer di kalangan anak muda sejak tahun 2019. Tujuan dari penelitian ini yaitu mengetahui karakteristik konsumen produk minuman boba khususnya mahasiswa Universitas Udayana Bukit Jimbaran, menganalisis  brand switching  dari beberapa merek minuman boba dalam lima tahun ke depan, serta menentukan keseimbangan pangsa pasar jangka panjang dari merek produk minuman boba. Penelitian ini dilakukan dengan survei langsung di gerai Chatime, Xiboba, dan Mixue Bukit Jimbaran. Penentuan sampel dilakukan dengan metode  purposive sampling , pengumpulan data berupa kuesioner, dan jumlah sampel menggunakan rumus Lemeshow sebanyak 100 responden. Metode analisis data dilakukan dengan metode rantai Markov dengan bantuan  software  POM-QM. Hasil penelitian menunjukkan karakteristik responden yang mengonsumsi produk minuman boba didominasi oleh perempuan berusia sekitar 18-24 tahun, besarnya pengeluaran untuk jajanan atau minuman berkisar antara Rp 100.000 – Rp 299.000 per bulannya, dengan rata-rata konsumsi minuman boba sebanyak 1 kali sebulan. Responden mendapatkan informasi tentang merek minuman boba melalui media sosial dan membeli produk minuman boba tanpa merencanakannya terlebih dahulu berdasarkan inisiatif sendiri. Pangsa pasar minuman boba periode 1 diketahui Chatime memimpin dengan pangsa pasar sebesar 47%, Mixue (41%), dan Xiboba (12%). Periode 2 terjadi peningkatan Chatime menjadi 47,2%, Mixue (43,6%), dan penurunan Xiboba (9,21%). Periode 3 dan seterusnya terjadi perubahan pangsa pasar pada masing-masing merek, dan pada periode 5 pangsa pasar Chatime mengalami peningkatan menjadi 48,6%, dan penurunan Xiboba (9,46%) dan Mixue (41,93%). Titik ekuilibrium diprediksi tercapai pada periode ke-5, dengan pangsa pasar Chatime sebesar 48,6%, Xiboba (9,5%), dan Mixue (41,9%). Kata kunci:  Brand switching , rantai Markov, Chatime, Xiboba, Mixue